The relationship between annual lung function decline and serum bilirubin levels in chronic obstructive pulmonary disease (Annals of Medical Research, 2025)
Aim: To study the relationship between the level of bilirubin in the serum and the annual decline in lung function in chronic obstructive pulmonary disease (COPD).Materials and Methods: The medical records of 1,574 patients diagnosed with COPD were reviewed in this retrospective study. In total, 126 eligible patients were included. Data from the initial visits and lung function tests performed at the end of the first year, along with serum direct bilirubin and total bilirubin (TB) measurements, were obtained from the electronic system and analyzed. Pearson correlation was used to determine the association between two continuous parameters.Results: Negative correlation was found between the annual changes in the first second of forced expiration (FEV1) percentage, FEV1 ml, predicted forced vital capacity (FVC) percentage, FVC ml, and predicted forced expiratory flow (FEF)25–75% percentage and the mean TB values and it was statistically significant (r: -0.202, -0.342, -0.236, -0.287, and -0.136, respectively). However, TB values did not have a significant relationship with the change in the FEV1/FVC ratio.Conclusion: The progression speed of COPD may vary among different patients. An elevated serum TB concentration within physiological limits could be considered a parameter that may slow the progression of COPD.
Keywords: Total bilirubin; Lung function test; COPD